Spontaneous Rupture of a Mediastinal Bronchial Artery Aneurysm Induced by Anticoagulant Agent - Wang, Zhimin; Xu, Chenghua; Ding, Xiaoxiao; Chen, Jinying; Xin, Huaping (The Thoracic and Cardiovascular Surgeon Reports, 2016)
Nontraumatic spontaneous rupture of a bronchial artery aneurysm is rarely seen. In this report, we described such a phenomenon in a patient induced by usage of anticoagulant agent. The patient had no antecedent history of trauma, hypertension, or apparent aortic pathology. The patient who had been taking low-molecular-weight heparin and warfarin to treat deep vein thrombosis complained of a sudden upper abdomen pain with shortness of breath and hypoxemia. The patient was diagnosed and treated for an acute hemomediastinum caused by a ruptured bronchial artery aneurysm. If the patient had continued to take the anticoagulant antithrombotic drugs, it may cause a more virulent bleeding. Taken together, CT angiography is a useful diagnosis tool for patients with sudden chest pain and abdominal pain, and rare cause should be considered.
Keywords: bronchial artery aneurysm; anticoagulant agent; spontaneous; rupture